Synthesis of Cu-(TAC) Composite with Oil Palm Empty Fruit Bunch Waste Activated Carbon Through the Adsorption Mechanism of Î²Carotene - Sari, Lidia Mutia; Jasmidi, Jasmidi; Nasution, Hafni Indriati; Zubir, Moondra; Rahmah, Siti; Selly, Rini; Faradilla, Putri (Universitas Negeri Medan, 2023)
This study aims to determine the adsorption and desorption abilities of activated carbon and Cu-(TAC) composites in the Î²-carotene adsorption process on Crude Palm Oil (CPO). Oil Palm Empty Fruit Bunches (EFB) are used as activated carbon and modified with MOFs Cu-(TAC). Activated carbon and Cu-(TAC) composites were characterized by XRD, SEM-EDX, and BET. The concentration of Î²-carotene absorbed during the adsorption process was analyzed using a UV-Vis spectrophotometer. The variations used to determine the optimum conditions for absorption of Î²-carotene were the mass variation of the adsorbent and the variation in the contact time between the adsorbent and adsorbate. The results of the characterization of activated carbon showed a sharp absorption in the presence of O-H, C-H and C-O groups indicating the presence of cellulose. Activated carbon is amorphous and the Cu-(TAC) composite has a crystal structure and its pore size is mesoporous. The optimum conditions for the use of activated carbon for Î²-carotene adsorption were the mass variation of 8 grams with 0.495 ppm of Î²-carotene and contact time at 120 minutes with 2.605 ppm of Î²-carotene. The optimum condition of the Cu-(TAC) composite in the Î²-carotene adsorption process was at 4 gram mass variation with 1.026 ppm Î²-carotene content and optimum contact time at 60 minutes with 6.384 ppm Î²-carotene content. The ability of desorption can be seen from the percentage of desorption showing activated carbon in the 150th minute with 96.252% while in the Cu-(TAC) composite in the 30th minute with 88.188%.